A Perspective on Sustainability Initiatives of a Swedish Outdoor Brand—An Interview with Lennart Ekberg from Haglöfs. (2nd July 2016) - Erdnüß, Lena
Abstract: This article takes a closer look at sustainability practices of a Swedish outdoor brand through an interview with the former Head of Sustainability at Haglöfs, Lennart Ekberg. The article takes on a critical perspective when examining Haglöfs' sustainability practices and reasons for implementing sustainable initiatives into their product development. It is shown that Haglöfs' main motivation for engaging in sustainable practices concerns three areas: a belief in a future demand for sustainable products, the hope of economic benefits, and to create a profile attracting young professionals. Throughout the interview it is also emphasized that the terminology of sustainability is an undefined issue. The article concludes that sustainability is an ever-evolving standard which will change over time, and one must realize that products claimed as being sustainable can still cause a negative impact on the environment.